Author Correction: 5-aminolevulinic acid-mediated photodynamic therapy can target aggressive adult T cell leukemia/lymphoma resistant to conventional chemotherapy - Yasuhisa Sando (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.